Biliary Stricture after Adult Right-Lobe Living-Donor Liver Transplantation with Duct-to-Duct Anastomosis: Long-Term Outcome and Its Related Factors after Endoscopic Treatment (Gut and Liver, 2010)
Background/Aims: Biliary stricture is the most common and important complication after right-lobe living-donor liver transplantation (RL-LDLT) with duct-to- duct biliary anastomosis. This study evaluated the efficacy and long-term outcome of endoscopic treatment for biliary stricture after LDLT, with the aim of identifying the factors that influence the outcome. Methods: Three hundred and thirty-nine adults received RL-LDLTs with duct-to-duct biliary anastomosis between January 2000 and May 2008 at Kangnam St. Mary's Hospital. Endoscopic retrograde cholangiography (ERC) was performed in 113 patients who had biliary stricture after LDLT. We evaluated the incidence of post-LDLT biliary stricture and the long-term outcome of endoscopic treatment for biliary stricture. The factors related to the outcome were analyzed. Results: Biliary strictures developed in 121 (35.7%) patients, 95 (78.5%) of them within 1 year of surgery. The mean number of ERCs performed per patient was 3.2 (range, 1 to 11). The serum biochemical markers decreased significantly after ERC (p＜0.001). Stent insertion or stricture dilatation during ERC was successful in 90 (79.6%) patients. After a median follow-up period of 33 months from the first successful treatment with ERC, 48 (42.5%) patients achieved treatment success and 12 (10.6%) patients remained under treatment. The factors related to the outcome of endoscopic treatment were nonanastomotic stricture and stenosis of the hepatic artery (p=0.016). Conclusions: Endoscopic treatment is efficacious and has an acceptable long-term outcome in the management of biliary strictures related to RL-LDLT with duct-to-duct biliary anastomosis. Nonanastomotic stricture and stenosis of the hepatic artery are correlated with a worse outcome of endoscopic treatment. (Gut Liver 2010;4:226-233)